Preserving Biodiversity of Sheep and Goat Farming in the Apulia Region - Antonella Santillo; Antonella della Malva; Marzia Albenzio (Animals)
The interconnection between biodiversity loss, food system and climate change is a complex issue with profound implications for global sustainability. Small ruminant farming is a crucial part of addressing these challenges as it contributes to environmental, social, and economic resilience. In Italy, sheep and goat farming is most common in marginal areas with a prevalence of pastoral systems and low mechanization levels. In the Apulia region of Southern Italy, autochthonous small ruminant breeds are at high risk of extinction, due to changing agricultural practices and market pressures. Autochthonous breeds represent valuable genetic resources, adapted to the local environment and capable of producing high-quality products. Apulia boasts an ancient dairy tradition, producing a variety of cheeses from small ruminants, such as Canestrato Pugliese, a Protected Designation of Origin, and four cheeses (Cacioricotta, Pecorino Foggiano, Scamorza di Pecora, and Caprino) recognized as Traditional Agri-Food Products by the Italian Ministry of Agriculture, Food Sovereignty and Forests. These products represent an essential element for biodiversity conservation, encompassing ecosystems, autochthonous breeds, microbial diversity, traditional farming practices, and production systems. This review surveys the main small ruminant native breeds of Apulia region, highlighting their historical significance, distinctive traits, and traditional productions, to help shape strategies for animal biodiversity conservation.